Respiratory tract infections among children younger than 5 years: current management in Australian general practice. Issue 5 (16th March 2015) - Biezen, Ruby; Pollack, Allan J; Harrison, Christopher; Brijnath, Bianca; Grando, Danilla; Britt, Helena C; Mazza, Danielle
Abstract: Objective: To explore the current management in Australian general practice of common respiratory tract infections (RTIs) in children younger than 5 years. Design, setting and participants: Analysis of data from a sample of 4522 general practitioners who participated in the Bettering the Evaluation and Care of Health (BEACH) cross‐sectional survey, April 2007 to March 2012. Consultations with children younger than 5 years were analysed. Main outcome measures: GPs' management of four common RTIs (acute upper RTI [URTI], acute bronchitis/bronchiolitis, acute tonsillitis, and pneumonia) in association with six management options: antibiotic medications; prescribed or supplied non‐antibiotic medications; medications advised for over‐the‐counter purchase; referrals; pathology testing; and counselling. Results: Of 31 295 encounters recorded, at least one of the four selected paediatric RTIs was managed at 8157 encounters. URTI was managed 18.6 times per 100 GP patient encounters, bronchitis/bronchiolitis 4.2 times, acute tonsillitis 2.7 times, and pneumonia 0.6 times per 100 encounters. Antibiotics were prescribed most frequently for tonsillitis and least frequently for URTI. Male GPs prescribed antibiotics for URTI significantly more often than female GPs, while older GPs prescribed antibiotics for URTI more often than younger GPs. Conclusion: GP management of paediatric RTIs in Australia varied according to the clinical problem and with age and sex of the GP. Further research into parents' and health professionals' attitudes and practices regarding the role of antibiotics, over‐the‐counter medications, and hygiene will help maintain favourable management practices.